PENGARUH KINERJA SISTEM KEUANGAN BANK SYARIAH TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH (STUDI BANK UMUM SYARIAH 2016-2019) - RAISYA PUSPA SEPTIANI; NURUL LAELANI (BALANCING: Accountancy Journal, 2021)
This study aims to examine the effect of the influence of financial performance which consists of Return To Asset (ROA), Financing of Deposit Ratio (FDR) and Operational Costs on Operating Income (BOPO) on the Profit Sharing Rate of Mudharabah Time Deposits. The population in this study is a Sharia bank registered on the Service Authority website Finance (OJK) 2016 to 2019. Data sources can be obtained from the official website of Otoritas Jasa Keuangan (OJK). Search Results www.ojk.go.id. as well as the website of Islamic Commercial Banks in Indonesia which were used as research samples. The sampling method used was a purposive sampling method. The number of samples in this study were 48 observations in 12 companies over a period of 4 years. The results of this study indicate that Return On Assets (ROA) has an effect on the profit sharing rate of mudharabah deposits and Operating Costs on Operating income (BOPO) have an effect on the profit sharing rate of mudharabah deposits.